DETERMINATION OF NUTRITIVE VALUE AND MINERAL ELEMENTS OF FICUS BENGHALENSIS LINN. SEED - GOVINDAN, VIMALA; SHOBA, FRANCIS GRICILDA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â ABSTRACT Objectives: This study was undertaken to assess the nutritive value and mineral contents of Ficus benghalensis seed locally prescribed as a diet for stomach ulcer. Methods: The nutrients were analyzed by using different biochemical methods while the mineral elements were analyzed by flame photometry and by using various titration methods. Results: Mineral element analysis revealed the presence of important macro and micro elements such as P, K, Na, Ca, Fe, Zn, Mg, Mn, Cu and Cr. The results for ash content, crude protein, crude carbohydrate, crude fat, crude fiber, vitamin C, and vitamin E content were 2.55%, 15.02%, 12.95%, 2.56%, 19.45%, 203.45Â±1.877 mg/g, 517.65Â±0.875 mg/g respectively. Nutritional value of F. benghalensis was 134.92Â±1.250 Cal/100 g. Conclusion: Our findings provide evidence that the selected plant seeds contain an appreciable amount of nutrients and minerals and can be included in diets to supplement our daily nutrient needs and to fight against many of the diseases as nutraceuticals. Keywords: Chemical analysis, Nutraceutical, Ficus benghalensis, Seed powder.